Curatorial Review; eCITRA19: Digital X Culture - Mohamad Faizuan, bin Mat (National Art Gallery, 2019)
The DigitalXCulture is a proposal about bringing cultural practices into the digital world. It ventures to reinvent how the revolution of digital media or materials or tools as a new element of presenting and defining cultural or local knowledge into a new method of design formation. Conceived to avoid the conventional definition in perceiving cultural or local knowledge into the effective methodology, where the revolution of digital media and digital era becomes a dialogue in re-understanding and re-processing the significances of cultures, local knowledge and approaches. Artists benefited both directly and indirectly from the impact of the IR4.0. The availability of technological wares like drones, augmented reality gadgets, virtual reality devices, high-end smartphones, 3D printers, mobile printers, invincible action cameras, and smart tablets allow artists to be more mobile, flexible, and creative with their creations. The impact of technology and machines on daily life seems impossible to ignore. Life seems to be moving at a faster pace, and artists sought to catch the fleeting moments and changes. For example, the field of photography was drastically affected by the development of technology. Camera Obscura has become historical, and the emergence of drone and high-end DSLR making the field of photography became exciting and challenging. Hence, it would be a force if we can highlight our cultural or local knowledge through the latest technology and digital medium.